2010
DOI: 10.1124/dmd.109.030676
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into UDP-Glucuronosyltransferase (UGT) Enzyme Kinetics of Imidazole- and Triazole-Containing Antifungal Drugs in Human Liver Microsomes and Recombinant UGT Enzymes

Abstract: ABSTRACT:Imidazoles and triazoles represent major classes of antifungal azole derivatives. With respect to UDP-glucuronosyltransferase (UGT) enzymes, the drug metabolism focus has mainly concentrated on their inhibitory effects with little known about azoles as substrates for UGTs. N-Glucuronide metabolites of the imidazole antifungals, tioconazole and croconazole, have been reported, but there are currently no reports of N-glucuronidation of triazole antifungal agents. In this study, evidence for glucuronidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 28 publications
2
36
1
Order By: Relevance
“…Expected CL R is the renal plasma clearance expected due to GFR if there was no reabsorption or tubular secretion (expected CL R  = fraction unbound × GFR =  f u  × 110 mL/minute). Metabolism was attributed to glucuronidation via UGT2B7, and unbound intrinsic clearance (CLnormalI) was calculated using hepatic clearance (CL H ) 24. The CL H was assumed to be 15% of total empiric clearance 23.…”
Section: Methodsmentioning
confidence: 99%
“…Expected CL R is the renal plasma clearance expected due to GFR if there was no reabsorption or tubular secretion (expected CL R  = fraction unbound × GFR =  f u  × 110 mL/minute). Metabolism was attributed to glucuronidation via UGT2B7, and unbound intrinsic clearance (CLnormalI) was calculated using hepatic clearance (CL H ) 24. The CL H was assumed to be 15% of total empiric clearance 23.…”
Section: Methodsmentioning
confidence: 99%
“…76 Voriconazole is also a low-affinity substrate for UGT1A4 in vitro. 49 An understanding of how genetic polymorphism affects voriconazole metabolism has been pivotal in explaining the pharmacokinetic variability observed in patients. The occurrence of genetic variants in the CYP alleles (Table 4) has a significant impact on the levels of drug achieved in those patients and probably upon the therapeutic efficacy of voriconazole.…”
Section: Anidulafunginmentioning
confidence: 99%
“…59 Recently, itraconazole was shown to be a substrate for the phase II enzyme UGT1A4, with an affinity similar to that of the imidazole antifungal agents, and it may also be an inhibitor of UGT1A4. 49 Itraconazole interacts with several genetically variable drug transporters and CYP enzymes, thus implicating them in the observed variability of itraconazole levels. Moreover, because CYP3A4 and P-glycoprotein also play a crucial role in the metabolism of many other drugs used in HSCT patients, this effect is likely to be compounded.…”
Section: Triazole Antifungalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The disposition and clearance of drugs may be significantly changed when UGT are modulated by co-administrated drugs or herbal medicines. For example, fluconazole itself is not metabolized by UGT but alter pharmacokinetic parameters of co-administrated zidovudine in AIDS patients, because the glucuronidation of zidovudine by UGT2B7 is strongly inhibited by fluconazole [12]; indinavir Although much research has been carried on the in vitro and in vivo metabolism profiles of AST and CAG, only a few articles that deal with metabolism enzymes elucidate the potential toxicity and herb-drug interactions. Shan et al [10] reported that AST was a competitive inhibitor of CYP2C9 and a non-competitive inhibitor of CYP3A4 in an in vitro study.…”
Section: Introductionmentioning
confidence: 99%